2009
DOI: 10.1007/s12600-009-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bacterial antagonists and different commercial products against Fusarium wilt on rocket

Abstract: Seven experimental trials were carried out to evaluate the efficacy of the bacterial strains Achromobacter xylosoxydans AM1 and Serratia sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…W 12 (Wu et al 2015). Research has confirmed that F. oxysporum is the pathogenic pathogens of R. glutinosa disease (Li et al 2013) and that most strains of Pseudomonas showed antagonistic activity against F. oxysporum (Borah et al 2015;Chin-A-Woeng et al 2000;Srinivasan et al 2009). In this work, we found that some congeneric species showed a close interaction with allelochemicals.…”
Section: Discussionsupporting
confidence: 53%
“…W 12 (Wu et al 2015). Research has confirmed that F. oxysporum is the pathogenic pathogens of R. glutinosa disease (Li et al 2013) and that most strains of Pseudomonas showed antagonistic activity against F. oxysporum (Borah et al 2015;Chin-A-Woeng et al 2000;Srinivasan et al 2009). In this work, we found that some congeneric species showed a close interaction with allelochemicals.…”
Section: Discussionsupporting
confidence: 53%
“…Some of these "Calcite Dissolving Bacteria" are Serratia marcescens, Sphingomonas changbaiensis, or Novosphingobium panipatense (Peper et al, 2022). Furthermore, the soil microbiome can become dominated by microbial assemblages that suppress the growth of AFL-producing fungi with increasing Ca2+ (Zhang et al, 2021), FUM-producing fungi (Srinivasan et al, 2009), and suppression of mycotoxin-producing fungi strains by non-toxin-producing fungi (Mehl et al, 2012;Ehrlich, 2014). The presence of both growth-suppressive bacteria and fungi that dissolve calcium carbonate would potentially lead to positive feedback in a calcium carbonate-rich soil.…”
Section: Discussionmentioning
confidence: 99%
“…Soil has untapped and several potential biocontrol agents that have shown high antagonistic activity against several soil-borne pathogens [34].The soil-inhabiting antagonists were found to be effective suppressant to Fusarium wilt of tomato and these include; nonpathogenic F. oxysporum [35], Trichoderma, Rhizoctonia, and Gliocladium [36], Bacillus species and Streptomyces species [37], Pseudomonas spp. [38]. Biological mechanisms through which the disease-suppressive soils control the disease development are illustrated in Fig.…”
Section: Use Of Suppressive Soilsmentioning
confidence: 99%